TINGKAT PENDIDIKAN DAN PENGETAHUAN TENTANG STATUS GIZI DENGAN ANGKA KEJADIAN STUNTING DI DESA BANJARSARI WETAN KEC. DAGANGAN KAB. MADIUN - Tintin Hariyani (Prosiding SPIKesNas : Seminar Publikasi Ilmiah Kesehatan Nasional, 2023)
Stunting is a toddler who experiences malnutrition in the first 1000 days of life, especially in the first 1000 days of life. The causes of stunting are poor parenting practices, lack of access to food, clean water, sanitation, knowledge of nutritional status and low levels of education. The purpose of this study was to determine the relationship between the level of education and knowledge of nutritional status with the incidence of stunting in Banjasrsari Wetan Village, Merchandise District, Madiun Regency.   This research uses analytic research design cross sectional. The variables of this study were education level and knowledge of nutritional status. The population of this study were all mothers who had toddlers as many as 210 respondents, using a sample of 136 respondents. The sampling technique used is probability sampling with simple random sampling technique. The instrument used is a questionnaire sheet. data were processed using the chi-square statistical test. The time of the research was carried out July 09 - July 22, 2022 at the Posyandu, Banjasrsari Wetan Village, Dagangan District, Madiun Regency.  The results showed that most of the respondents (72.7%) who had elementary and junior high school education experienced stunting in their children, almost all of the respondents (90.6%) who had a low level of knowledge about nutritional status experienced stunting in their children, and a small portion of the respondents (25.0%) experienced stunting. The results of the analysis show a p value 0.000 (p <0.05), which means that there is a relationship between the level of education and knowledge of nutritional status with the incidence of stunting in Banjasari Wetan Village,Dagangan District, Madiun Regency, with a strong correlation (correlation coefficient -0.665 and -0.691).